Project-based experience through real manufacturing activities in mechanical engineering. Issue 1 (January 2020) - Abellán-Nebot, José V
As reported by many professional bodies responsible for accrediting engineering programs, today's engineering graduates present important limitations in the practice of engineering because current engineering curricula are still too focused on fundamental engineering science without providing sufficient integration to industrial practice. To overcome these limitations, active learning approaches have been applied in the literature with positive results in engagement, motivation and student's performance. In this paper, we propose a project-based learning approach with real manufacturing activities in a four-year mechanical engineering course to improve the learning process. The goal of the project is to plan the manufacturing process of a real part and conduct at shop-floor levels all the activities required. The experience was evaluated considering project/exam grades, questionnaires and manufacturing quality. The results showed an increase in student's satisfaction, improvement in the exam performance and a clear increase in student's enrolment in the manufacturing master degree.